2014
DOI: 10.1038/nature13921
|View full text |Cite
|
Sign up to set email alerts
|

An AUTS2–Polycomb complex activates gene expression in the CNS

Abstract: SummaryNaturally occurring variations of Polycomb Repressive Complex 1 (PRC1) comprise a core assembly of Polycomb group proteins and additional factors that include, surprisingly, Autism Susceptibility Candidate 2 (AUTS2). While AUTS2 is often disrupted in patients with neuronal disorders, the underlying mechanism is unclear. We investigated the role of AUTS2 as part of a previously identified PRC1 complex (PRC1-AUTS2), and in the context of neurodevelopment. In contrast to the canonical role of PRC1 in gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
400
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(419 citation statements)
references
References 46 publications
14
400
3
2
Order By: Relevance
“…It remains to be determined in detail how other PRC1 complex components, or regulatory mechanisms such as activating phosphorylation of PCGF proteins 53,54 or inactivating phosphorylation of RING1B within PRC1.5 (ref. 55), influence E3 ligase activity of canonical and non-canonical PRC1.…”
Section: Article Nature Communications | Doi: 101038/ncomms8621mentioning
confidence: 99%
“…It remains to be determined in detail how other PRC1 complex components, or regulatory mechanisms such as activating phosphorylation of PCGF proteins 53,54 or inactivating phosphorylation of RING1B within PRC1.5 (ref. 55), influence E3 ligase activity of canonical and non-canonical PRC1.…”
Section: Article Nature Communications | Doi: 101038/ncomms8621mentioning
confidence: 99%
“…The CK2 subunit of the complex neutralizes PRC1 repressing activity and subsequent recruitment of P300 by AUTS2 leads to neural gene activation [313]. Similar activating function of PRC1s was described in spermatogenesis.…”
Section: The Activator Function Of Ncprc1s Opens New Perspectives In mentioning
confidence: 68%
“…Notably, at molecular level, the H2AK119ub1 levels of the Pcgf5 null mutants were reduced in comparison to the control but this reduction had no effect on global gene expression. Genome-wide studies suggested that PRC1.5 complexes encompassing CK2 and AUTS2 are recruited to active genes, uncovering a new function of the PRC1.5 in activating transcription ( [313] and see below). [148,306,307,310] CK2 belongs to the serine/threonine-selective protein kinase family.…”
Section: Ncprc13 and Ncprc15mentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, AUTS2 plays a role in regulation of neuronal gene expression through promoter association. Their hypothesis is that changes in AUTS2 result in reduced neuronal gene expression trough the AUTS2 ‐PRC1 complex and can give different developmental defects 10. Polycomb group proteins play an important role in neurodevelopment, but deregulation can lead to oncogenesis.…”
Section: Discussionmentioning
confidence: 99%